Association of cleft lip and palate on mother-to-infant bonding: a cross-sectional study in the Japan Environment and Children’s Study (JECS) - Shinobu Tsuchiya; Masahiro Tsuchiya; Haruki Momma; Takeyoshi Koseki; Kaoru Igarashi; Ryoichi Nagatomi; Takahiro Arima; Nobuo Yaegashi; Japan Environment & Children’s Study Group (BMC Pediatrics, 2019)
Abstract Background Cleft lip and/or palate is among the most prevalent congenital birth defects, and negatively affects maternal psychological status and may consequently result in higher prevalence of child maltreatment. However, the association of childbirths of infants with cleft lip and/or palate with maternal emotional involvement still remains unclear. We examined the association between childbirths of infants with cleft lip and/or palate and mother-to-infant bonding, using data from the Japan Environment and Children’s Study, a nationwide birth cohort study. Methods A cross-sectional study using the jecs-an-20,180,131 dataset was performed. A total 104,065 fetuses in 15 regional centres in Japan were enrolled after obtaining informed written consent. The Mother-to-Infant Bonding Scale, a self-report scale consisting of 10 items, was used to evaluate maternal bonding at one year after childbirth. Finally, the participants consisted of 79,140 mother-infant pairs, of which 211 mothers of infants with cleft lip and/or palate were included in our analyses. Multivariable logistic regression analysis using multiple imputation for missing data was performed to calculate the odds ratio and 95% confidence interval in the estimation of the association between bonding disorders and childbirths with cleft lip and/or palate. Results No increased risk of bonding disorders was observed among all the mothers of infants with cleft lip and/or palate (odds ratio [95% confidence interval]; 0.97 [0.63–1.48], p = 0.880), however, advanced maternal age or multiple parity may adversely affect the associations between bonding disorders and cleft lip and/or palate, respectively. After stratification with a combination of maternal age and parity, a significant association of cleft lip and/or palate with bonding disorders was found only among advanced-age multiparae (odds ratio [95% confidence interval] = 2.51 [1.17–5.37], p = 0.018), but it was weakened after additional adjustment for maternal depression. Conclusions Childbirths of infants with cleft lip and/or palate may increase the risk of bonding disorders among advanced-age multiparae, possibly through maternal depression. This finding provides valuable information for the provision of multidisciplinary cleft care.